Physical Phenomena to Promote The Learning of Physics in Mexican Preschool Education - Mario Humberto Ramírez Díaz; Ana Rosa Barrón Hernández (Journal of Physics Education and Science, 2025)
The idea of global interdependence and solidarity, which must unite us as a society for the peaceful and equitable promotion of a sustainable future, is one of the main arguments that international organizations have raised and are intensely dedicated to researching and building systems around the world. However, few countries have managed to leave behind the “impressive curricula” of science, in which the idea is conveyed that it is made by and for superhumans, resulting in few choosing a career in science. Given this situation and the technological advances brought about by AI, it is important to rethink the teaching of physics in Mexico. Physics is still considered an unattractive, inaccessible subject with little exploration in basic education; despite it is one of the favourite sciences of people who, in the early stages of their development and without knowing that it is physics, show great interest in the phenomena that surround them. These are some of the questions that children explore and try to explain. But today there are no solid and contemporary strategies that address and investigate this theme to make possible to promote physics from an early age for children and the training of teachers